Analysis of Resources in Achieving the Healthy Family Index at the Selatbaru Public Health Center, Bengkalis Regency in 2021 - Asmala Sari; Nurvi Susanti; Hastuti Marlina; Jasrida Yunita; Mishbahuddin Mishbahuddin (Budapest International Research and Critics University, 2022)
The purpose of this research is to discuss about analysis of resources in achieving the healthy family index at the Selatbaru Public Health Center, Bengkalis Regency in 2021. This type of research is qualitative with descriptive analysis. The research informants are 12 people consisting of 1 key informant, namely the Head of the Public Health Center, 8 main informants, namely the Manager of the Healthy Indonesia Program with the Family Approach, Manager of the Maternal and Child Health Program, Manager of the Nutrition Program, Manager of the Tuberculosis Program, and Program Manager of Non-Communicable Diseases, Mental Program Manager, Environmental Health Program Manager, Health Promotion Program Manager, and 3 supporting informants namely the Health Service Section of Primary Health Services, District Secretary, and Village Head. Data collection methods are interviews, observation, and document review. The data analysis technique used content analysis. The results show that cross-sectoral integration in supporting achieving the healthy family index at the Selatbaru Public Health Center, Bengkalis Regency in 2021 is still not optimal and needs to be improved.